Social Networking Sites and Empathy Among Adolescents in Indonesia - Cut Tina Meuthia; Sarah Nila; Bambang Suryobroto; Kanthi Arum Widayati (Bogor Agricultural University, Indonesia, 2023)
Social networking sites (SNSs) have increased in number and popularity for more than a decade especially for adolescents. Previous studies conducted in western countries have stated that using SNSs could exert positive and negative effects on various aspects of psychosocial development, one of which is empathy. The relationship between SNSs use and empathy has remained unclear, especially in Indonesia. Therefore, the present study aims to determine the relationship between SNSs and empathy on adolescents in Indonesia. This study recruited 1,638 students from junior and senior high school with ages ranging from 12 to 19 years randomly across several provinces in Indonesia. Data collection was carried out by administering online questionnaires to participants consists of informed consent, demographic data, intensity of SNSs use during the past week with the Social Networking Time Use Scale (SONTUS) method, and questions about empathy with the Adolescent Measure of Empathy and Sympathy (AMES) method. Our result showed that higher frequency of using SNSs significantly positive correlated with cognitive empathy, affective empathy, and sympathy among adolescents in Indonesia, which is similar to previous studies, so this may be a general pattern in adolescence. The connections made by SNSs is believed to increase feelings of humanity (sympathy) and also empathy to other humans.